2022
DOI: 10.1111/nyas.14766
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation ameliorates maternal diabetes–mediated gastrointestinal symptoms and autism‐like behavior in mouse offspring

Abstract: Epidemiological studies have shown that maternal diabetes is associated with autism spectrum disorder development, although the detailed mechanism remains unclear. We have previously found that maternal diabetes induces persistent epigenetic changes and gene suppression in neurons, subsequently triggering autism-like behavior (ALB). In this study, we investigated the potential role and effect of hematopoietic stem cells (HSCs) on maternal diabetesmediated gastrointestinal (GI) dysfunction and ALB in a mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Furthermore, our previous study showed that prenatal factor exposure mediates gene suppression in hypothalamus, hippocampus and amygdala, especially the amygdala plays a dominant role in ALB (Zou et al, 2017); therefore, we focus on the potential effect in amygdala and related gene expression in this work. In addition, we have previously found that prenatal factor exposure‐mediated oxidative stress (Liu et al, 2022) and epigenetic changes can also happen in hematopoietic stem cells (HSCs), and this can be inherited by PBMCs during subsequent embryonic differentiation (Lu et al, 2020; Zeng et al, 2022). In this case, the gene expression from both HSC and PBMC was determined from prenatal factor exposure‐mediated offspring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our previous study showed that prenatal factor exposure mediates gene suppression in hypothalamus, hippocampus and amygdala, especially the amygdala plays a dominant role in ALB (Zou et al, 2017); therefore, we focus on the potential effect in amygdala and related gene expression in this work. In addition, we have previously found that prenatal factor exposure‐mediated oxidative stress (Liu et al, 2022) and epigenetic changes can also happen in hematopoietic stem cells (HSCs), and this can be inherited by PBMCs during subsequent embryonic differentiation (Lu et al, 2020; Zeng et al, 2022). In this case, the gene expression from both HSC and PBMC was determined from prenatal factor exposure‐mediated offspring.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the gene expression from both HSC and PBMC was determined from prenatal factor exposure‐mediated offspring. In order to evaluated the ALBs in mouse offspring, the ultrasonic vocalization (USV), social interaction (SI) test and three‐chambered social test were employed based on our previous report (Wang et al, 2019; Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that transplantation of HSC with SOD2 expression can partly reverse maternal diabetes‐induced ALB and GI dysfunction, indicating that HSCT with related gene manipulation may be a potential choice for treatment [24]. In this study, we found that HSCT with CLDN1 expression can partly reverse prenatal 17‐OHPC exposure‐mediated GI dysfunction, but has no effect on ALB, indicating that CLDN1 suppression in IEC may partly contribute to prenatal 17‐OHPC exposure‐mediated GI dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have explored the relationship between metabolic disorders and psychiatric disorders, and there has been a gradual increase in research on the relationship between diabetes and psychiatric disorders, as well as a large body of literature exploring the effect of maternal diabetes on the development of neurodevelopmental disorders in offspring (61)(62)(63)(64)(65), but the detailed mechanisms remain unclear. Meanwhile, there are fewer original studies on the comorbid psychiatric disorders in patients with T1DM.…”
Section: Discussionmentioning
confidence: 99%